1987
DOI: 10.1111/j.1365-246x.1987.tb01374.x
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude and phase data inversions for phase velocity anomalies in the Pacific Ocean basin

Abstract: Rayleigh wave phase velocities at periods 30-80 s in the Pacific Ocean are calculated by inverting phase and amplitude anomaly data using the paraxial ray approximation and the Gaussian beam method. The region is divided into 5"x 5" blocks, and approximately 200 source-receiver pairs from 18 well-studied events around the Pacific Ocean are used. First, we assume phase anomalies for the lithospheric age-dependent model. Next, conventional phase data inversions are conducted assuming great circle paths so that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 29 publications
1
51
0
Order By: Relevance
“…Using ray theory, Woodhouse & Wong (1986) showed that anomalous surface wave amplitudes can be caused by focusing or defocusing due to lateral refraction. Similar results were obtained by Yomogida & Aki (1987) for an inversion of Rayleigh wave across the Pacific Ocean using the Gaussian beam method. The ray tracing results of both studies indicate that ray paths can significantly deviate from the great circle.…”
Section: Introductionsupporting
confidence: 85%
“…Using ray theory, Woodhouse & Wong (1986) showed that anomalous surface wave amplitudes can be caused by focusing or defocusing due to lateral refraction. Similar results were obtained by Yomogida & Aki (1987) for an inversion of Rayleigh wave across the Pacific Ocean using the Gaussian beam method. The ray tracing results of both studies indicate that ray paths can significantly deviate from the great circle.…”
Section: Introductionsupporting
confidence: 85%
“…Such an approach was used, for example, by Yomogida & Aki (1987) recently. However, this approach is not quite correct according to our formulation in the previous section, although the solution cannot be grossly wrong.…”
Section: Directional Dependence Of Scatteringmentioning
confidence: 98%
“…Ray-theory is a high frequency approximation, however, which is not justi ed in the presence of heterogeneities whose length-scale is comparable to the wavelength of the wave e.g., Woodhouse, 1974;Wang & Dahlen, 1995. For the ray approximation to be valid, the rst Fresnel zone must be smaller than the scale-length of the heterogeneity, which places limitations on the lateral resolution of seismic models based on ray-theory. The Born or Rytov approximation for surface wave scattering e.g., Woodhouse & Girnius, 1982;Yomogida & Aki, 1987;Snieder & Romanowicz, 1988;Bostock & Kennett, 1992;Friederich et al, 1993, Friederich 1999Meier et al, 1997;Spetzler et al, 2001Spetzler et al, , 2002Yoshizawa & Kennett, 2002;Snieder, 2002 models the nite width of the surface wave sensitivity zone. Ritzwoller et al 2002 discussed the use of this approximation in the context of global surface wave tomography, calling the resulting method global di raction tomography.…”
Section: Introductionmentioning
confidence: 99%